GAMBARAN PENERIMAAN APLIKASI PUSKESMAS TANPA ANTRIAN (PUSTAKA) DENGAN TECHNOLOGY ACCEPTANCE MODEL DI PUSKESMAS ROWOSARI SEMARANG - Lutfiyah Rizqulloh; Muhammad Iqbal (Politeknik Negeri Jember, 2022)
Health Center services must implement electronic services in line with technological advances. The Semarang City Health Office has now implemented mobile health with the launch of the Semarang City No Queue Health Center Program (PUSTAKA) in 2018. The presence of PUSTAKA makes people not have to queue long to get health services at the Semarang City Health Center. Based on data obtained from the Semarang City Health Office in 2018-2020, the results of the recap of the number of users of the PUSTAKA system in all health centers in 2018 were 8,558 users; in 2019, the use of the PUSTAKA system has increased with the number of users as much as 59,500 users, but in 2020 The number of PUSTAKA users has decreased again with a total of 50,597 users. The research benefits are expected to be used to see the description of PUSTAKA implementation at the Rowosari Health Center Semarang. The study was conducted at the Rowosari Public Health Center Semarang with 145 respondents using a non-probability sampling technique. The research variables are Perceived Usefulness, Perceived Ease of Use, Behavioral Intention to Use, and Attitude Toward Using. The results showed that the public's interest was very high in using the PUSTAKA application at the Rowosari Health Center